199k views
2 votes
Solve for b. a = 9b2c

User Wviana
by
4.2k points

1 Answer

5 votes

Answer:

±sqrt(ac)

---------- = b

3c

Explanation:

a= 9b^2 c

Divide each side by 9c

a/9c = 9b^2c / 9c

a/9c= b^2

Take the sqrt of each side

±sqrt(a/9c) = sqt(b^2)

Remember that sqrt (xy) = sqrt(x) sqrt(y)

±sqrt(a/c) * 1/ sqrt(9) = b

±sqrt(a) 1

--------- * ------ = b

sqrt(c) 3

Multiply by sqrt(c)/ sqrt(c)

±sqrt(a) sqrt(c)

--------- * ----------- = b

sqrt(c) 3sqrt(c)

±sqrt(ac)

---------- = b

3c

User Efaruk
by
4.9k points